The CD8+ T-cell response to lymphocytic choriomeningitis virus involves the L antigen: uncovering new tricks for an old virus - Kotturi, Maya F; Peters, Bjoern; Buendia-Laysa, Jr, Fernando; Sidney, John; Oseroff, Carla; Botten, Jason; Grey, Howard; Buchmeier, Michael J; Sette, Alessandro (Journal of virology, 2007)
CD8(+) T-cell responses control lymphocytic choriomeningitis virus (LCMV) infection in H-2(b) mice. Although antigen-specific responses against LCMV infection are well studied, we found that a significant fraction of the CD8(+) CD44(hi) T-cell response to LCMV in H-2(b) mice was not accounted for by known epitopes. We screened peptides predicted to bind major histocompatibility complex class I and overlapping 15-mer peptides spanning the complete LCMV proteome for gamma interferon (IFN-gamma) induction from CD8(+) T cells derived from LCMV-infected H-2(b) mice. We identified 19 novel epitopes. Together with the 9 previously known, these epitopes account for the total CD8(+) CD44(hi) response. Thus, bystander T-cell activation does not contribute appreciably to the CD8(+) CD44(hi) pool. Strikingly, 15 of the 19 new epitopes were derived from the viral L polymerase, which, until now, was not recognized as a target of the cellular response induced by LCMV infection. The L epitopes induced significant levels of in vivo cytotoxicity and conferred protection against LCMV challenge. Interestingly, protection from viral challenge was best correlated with the cytolytic potential of CD8(+) T cells, whereas IFN-gamma production and peptide avidity appear to play a lesser role. Taken together, these findings illustrate that the LCMV-specific CD8(+) T-cell response is more complex than previously appreciated.